Description of an unusual new Costa Rican species of Cerodontha (Dizygomyza) with additional notes on Neotropical species of Dizygomyza (Diptera: Agromyzidae) - Boucher, Stéphanie (Zootaxa, 2005)
Cerodontha (Dizygomyza) nigrihalterata sp. nov. is described from Costa Rica. This species is unusual in having black halteres, the presence of only one upper orbital seta and infuscated wings. Two additional species of Dizygomyza are newly recorded from the Neotropical region: Cerodontha (Dizygomyza) luctuosa (Meigen) and Cerodontha (Dizygomyza) scirpioides Zlobin. Two Neotropical species of Cerodontha previously assigned to Dizygomyza are reassigned to subgenus Butomomyza: Cerodontha (Butomomyza) puertoricencis Spencer new comb. and Cerodontha (Butomomyza) orcina Spencer new comb.